Research on the development and differentiation of the physical literacy scale for Chinese college students - Rongjing Ni; Ying Yu (PLoS ONE, 2026)
Objectives To understand the current status and characteristics of physical literacy among Chinese college students, develop a measurement scale suitable for this population, and provide an appropriate assessment tool for related research. Methods The Delphi method and a questionnaire survey were initially employed to screen and evaluate the reliability and validity of 53 preliminary items. Subsequently, the finalized measurement tool, which had been assessed for reliability, was administered to 3,077 Chinese college students via a questionnaire survey to identify population variation characteristics. Results Following a systematic screening process, the reliability coefficients for the four dimensions ranged from 0.731 to 0.821, and a reliable measurement tool for assessing physical literacy among Chinese college students was established. The final scale comprises four dimensions—physical activity capacity, physical activity behavior, physical activity cognition, and emotional experience—with a total of 32 items. The survey revealed significant differences in physical literacy among Chinese college students across the following dimensions: gender (t = 24.914, P < 0.001), household registration (t = 11.464, P < 0.001), grade (F = 30.811, P < 0.001), university category (F = 17.305, P < 0.001), and university district (F = 4.957, P < 0.01). Furthermore, significant differences were observed to varying degrees across all four dimensions—physical activity capacity, physical activity behavior, physical activity cognition, and emotional experience. Conclusion The developed Physical Literacy Scale for Chinese College Students is suitable for research targeting this population. The survey revealed significant differences in physical literacy levels among Chinese college students based on gender, grade, household registration, university category, and university district.